A new proterochampsid (Archosauriformes: Proterochampsia) from the Late Triassic of southern Brazil and the emergence of archosaurian hind limb traits. (31st December 2022) - Müller, Rodrigo Temp; Garcia, Mauricio Silva; Fonseca, André de Oliveira
Abstract : Characterized by an elongated snout, proterochampsids are carnivorous non-archosaur archosauriforms. The clade is endemic to South America and its fossil record extends from the early Carnian to the late Carnian/early Norian. Nesting close to Archosauria, it is a key clade for understanding the origin and evolution of archosaurian traits. Unfortunately, hind limb elements are usually poorly preserved for the group. Therefore, the hind limb anatomy of proterochampsids still lacks detailed descriptions. In the present study, we partially fill this gap with the description of a new proterochampsid represented by a complete and well-preserved hind limb. Stenoscelida aurantiacus gen. et sp. nov. was excavated from the late Carnian/early Norian (Late Triassic) beds of southern Brazil. A phylogenetic investigation recovers the new taxon as a non-rhadinosuchine proterochampsid. The species bears an unusual set of traits for the group, which provides clues on the evolutionary origins of some muscle attachment structures. For instance, the femur of Stenoscelida aurantiacus gen. et sp. nov. possesses an anterior trochanter and an anterolateral scar. So far, these features have not been reported in other non-archosaurian archosauriforms. Therefore, the new specimen indicates that some typical archosaurian features evolved earlier than previously thought. The taxon also carries additional uncommon features for proterochampsids, such as an iliofibularis tubercle on the anterior margin of the fibula and a vestigial phalanx in digit V. In sum, Stenoscelida aurantiacus has one of the best-preserved hind limbs within Proterochampsidae and sheds light on the polarization of important traits regarding the evolutionary context of Archosauria. http://zoobank.org/urn:lsid:zoobank.org:pub:C78B7CE3-AB9B-4543-833E-B2A3FEA957D9